Energy Biographies: Narrative Genres, Lifecourse Transitions, and Practice Change. (May 2016) - Groves, Christopher; Henwood, Karen; Shirani, Fiona; Butler, Catherine; Parkhill, Karen; Pidgeon, Nick
The problem of how to make the transition to a more environmentally and socially sustainable society poses questions about how such far-reaching social change can be brought about. In recent years, lifecourse transitions have been identified by a range of researchers as opportunities for policy and other actors to intervene to change how individuals use energy, taking advantage of such disruptive transitions to encourage individuals to be reflexive toward their lifestyles and how they use the technological infrastructures on which they rely. Such identifications, however, employ narratives of voluntary change that take an overly optimistic view of how individuals experience lifecourse transitions and ignore effects of experiences of unresolved or unsuccessful transitions. Drawing on interview data from the Energy Biographies project at Cardiff University, we explore three case studies where the effects of such unresolved transitions are significant. Using the concept of liminal transition as developed by Victor Turner, we examine instances where "progressive" narratives of energy use reduction clash with other "narrative genres" used to make sense of change. Such clashes show how narratives that view lifecourse transitions as opportunities ignore the challenges that such transitions may pose to efforts to construct or sustain identities.